2009
DOI: 10.1155/2009/340953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Power Lines on Area Use and Behaviour of Semi-Domestic Reindeer in Enclosures

Abstract: We conducted large-scale, replicated experiments to test the effects of two parallel power lines on area use, behaviour, and activity of semidomestic reindeer in enclosures. Yearling female reindeer were released into four 50 × 400 m enclosures; two treatment enclosures with power lines and two control enclosures. Reindeer from two herds, one from Kautokeino (domestic tame) and one from Vågå, (domestic wild) were tested separately and compared. Individual location within the enclosures was not affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…As in studies of wild reindeer (e.g. Hanson 1981; Reimers and Svela 2001), few signs of avoidance or disturbance were found for domesticated reindeer at this scale of perception (Flydal et al 2004(Flydal et al , 2009). Baskin and Hjältén (2001) found that domesticated reindeer had a shorter flight distance than wild reindeer, but still they fled from an approaching person.…”
Section: Relevance Of a Large-scale Perspective For Domesticated Reinsupporting
confidence: 67%
See 1 more Smart Citation
“…As in studies of wild reindeer (e.g. Hanson 1981; Reimers and Svela 2001), few signs of avoidance or disturbance were found for domesticated reindeer at this scale of perception (Flydal et al 2004(Flydal et al , 2009). Baskin and Hjältén (2001) found that domesticated reindeer had a shorter flight distance than wild reindeer, but still they fled from an approaching person.…”
Section: Relevance Of a Large-scale Perspective For Domesticated Reinsupporting
confidence: 67%
“…A regional study could, therefore, include all scales of selection from region to patch, while an intermediate study could include both the landscape and patch scale of selection. Two studies by Flydal et al (2004Flydal et al ( , 2009 were defined as strictly local as they describe observations over a shorttime period, involving a few individuals in enclosures with a wind turbine and two parallel high voltage power lines, respectively. The short-term observations consisted of scan and focal sampling of animals.…”
Section: Local Scalementioning
confidence: 99%
“…), elk (Cervus canandensis) and other ungulates fed in a power line ROW (500 kV, 41 m wide) without signs of disturbance apart from a five-minute motionless period when entering the ROW (Goodwin Jr, 1975). Also semidomestic reindeer in an enclosure experiment did not clearly avoid power lines (132 and 300 kV) (Flydal et al, 2009).…”
Section: Visual Distractionmentioning
confidence: 90%
“…Fluctuations in electric fields of a 500 kV power line did not influence cattle behaviour (Ganskopp et al, 1991). Domestic-tame reindeer in enclosures became more restless and moved away from power lines (132 and 300 kV) when transmission load increased, although these results were ambiguous (Flydal et al, 2009).…”
Section: Electromagnetic Fieldsmentioning
confidence: 96%
See 1 more Smart Citation